The Role of Military Training in Improving Psychological Resilience and Reducing Depression Among College Freshmen - Guo, Rui; Sun, Meng; Zhang, Chi; Fan, Zebin; Liu, Zhening; Tao, Haojuan (Frontiers in Psychiatry, 2021)
Background: Military-style training, which was conducted for college freshmen each year, are considered as a form of hardiness training which may enable one to withstand negative stress. However, the effects of military-style training on psychological resilience and depression among college freshmen remain unclear. The present study aimed to evaluate changes in psychological resilience and depression through military-style training among college freshmen, and to investigate associated psychosocial factors including childhood trauma that may influence its effects on psychological resilience. Methods: It was a prospective and self-comparison design study. College freshmen who received 3 weeks of military-style training was recruited. Socio-demographic variables were collected and childhood trauma exposure was estimated by Childhood Trauma Questionnaire (CTQ). The Connor-Davidson Resilience Scale (CD-RISC) and Patient Health Questionnaire (PHQ-9) were used to assess psychological resilience and depression before and after the military-style training. Results: The total and subscale scores of CD-RISC were significantly increased (p < .001) while the scores of PHQ-9 was decreased (p < .001) after the military-style training program compared with those before the training. The proportion of students with clinical depression was reduced from 10.5% at baseline to 7.2% after the training (p < .001). Male and urban area played positive roles in the improvement of CD-RISC scores, while older age, higher baseline scores of PHQ and CTQ were adverse factors. Significant correlation was found between changes in scores of CD-RISC and PHQ-9 through the training (r = -0.238, p < .001) Conclusions: Military-style training may have positive effect on increasing psychological resilience and reducing depressive symptoms among college freshmen, especially in male students and those from urban area, while older age, childhood trauma, higher depression levels and resilience at baseline may weaken, or even mask its positive effect. Follow-up research should be considered on the long-term effects of military-style training.